External Influence : China’s soft power and the belt and road initiative in Southeast Asia - Muhammad Haikal Hasbullah (Nanyang Technological University, 2020)
President Xi has heightened China’s soft power capabilities and usage of public diplomacy to improve its image and influence in the region, in a bid to ensure the success of the Belt and Road Initiative (BRI). Given this shift in China’s approach to the BRI via soft power, it is imperative to study whether there is a correlation between soft power and the extent of its impact on the success of the BRI in terms of its progress and completion. Based on the surveys conducted by ISEAS – Yusoff Ishak Institute and data provided by AidData, the findings from this essay supports the presence of a correlation as the improvements and usage of soft power has undoubtedly helped the expansion of the BRI in Southeast Asia. However, the effects of soft power have been affected by various factors such as the issues in the BRI as well as the domestic factors in the recipient countries.